Case Report: Surgical Therapy for Left Innominate Vein Aneurysm Under Thoracoscopy - Hu, Yan; Ren, Siying; Zeng, Chao; Li, Jina; Zou, Min; Wang, Li; Xiao, Peng; Yu, Fenglei; Liu, Wenliang (Frontiers in Surgery, 2021)
Left innominate vein aneurysm is extremely rare, with a limited number of case reports present in the literature. Herein, we report a case of a 50-year-old female patient presenting with an incidental finding of an anterior mediastinal mass on chest radiography during a routine health examination. Contrast-enhanced computerized tomography (CT) of the chest showed a 4.8  4.6 cm anterior mediastinal mass with significant homogenous enhancement after injection of the contrast medium, suggesting a diagnosis of Castleman's disease, but not excluding thymoma. The patient underwent surgical resection of the anterior mediastinal mass under a thoracoscopic approach. Postoperative pathology confirmed the diagnosis of a left innominate vein aneurysm. This is the first case reporting a left innominate vein aneurysm resected under thoracoscopy. Despite this successful treatment experience, we need to emphasize that open thoracotomy or median sternotomy should be chosen as the first choice for surgeons who lack experience in thoracoscopic surgery, with the aim of avoiding intraoperative accidents.